Inelastic heat fraction estimation from two successive mechanical and thermal analyses and full-field measurements - T. Pottier (2018)
A new method to identify inelastic heat fraction (b factor) evolution models is proposed in this paper. It is based on: (i) simultaneous kinematic and thermal field measurements on heterogeneous tensile tests and (ii) Finite Element Updating (FEU) inverse method. Two inverse calculations, that involve a LevenbergeMarquardt optimization algorithm, are successively used to identify on the one hand the material parameters of a mechanical constitutive model (anisotropic plasticity coefficients and hardening parameters) and on the other hand the plastic power ratio converted into heat. The power balance of the thermomechanical problem is calculated and presented, and the assessment of thermal heat sources is detailed. Finally, six mechanical parameters and four evolution models of b are successively identified for commercially pure titanium. Results confirm a strain dependency of b. © 2012 Elsevier Masson SAS. All rights reserved.